Peningkatan Kemampuan Membaca Peta Konsep Buku Fiksi Dengan Menggunakan Metode SQ3R Pada Siswa Kelas VIII F SMPN 1 Bringin - Yuvinda Eka Anggita Putri; Eni Winarsih; Kamiran (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study aims to improve the ability to read fiction book concept maps using the SQ3R method in grade VIII F students of SMPN 1 Bringin. The type of research applied is classroom action research. The subjects of this study were 36 students of grade VIII F SMPN 1 Bringin, including 20 female students and 16 male students. Data collection techniques use observation and documentation. Data analysis techniques use qualitative descriptive. The results showed that the skill of reading fiction book concept maps in grade VIII F students of SMPN 1 Bringin increased after using the SQ3R method. These results can be known through improvements in the learning process and increased student understanding related to fiction book concept maps. The test results showed an average pre-action score of 63,27. This value increased in cycle I with a total of 68,83. In the second cycle stage, there was also an increase of 79,30 with a percentage of 100% completeness. Keywords: Concept Map; SQ3R; Classroom Action Research.